019 A program of research to increase research access and participation for children and young people with life-limiting conditions and life-threatening illnesses: 'barriers to research access: voices, experiences, and solutions- the BRAVES project'. (December 2018) - Butler, A; Vincent, K; Bluebond-Langner, M
Abstract : Background: A recent study of recruitment practices in paediatric palliative care research found that clinicians selectively recruited families, preventing them from making their own choice about research participation. Recognising this as a broader problem, we developed a multi-pronged approach to explore barriers to research participation for children and young people with life-limiting conditions and life-threatening illnesses (CYP with LLC/LTIs). Aims: The BRAVES project aims to understand barriers to research with CYP with LLC/LTIs, and develop guidance to further enable the research process. Methods: The BRAVES project uses a mixed methods approach, and involves five work-packages: A systematic review exploring recruitment practices in research with CYP with LLC/LTIs A survey of palliative care clinicians' perceptions of barriers to research with children A national survey of chief investigators' (CIs) experiences conducting studies involving CYP with LLC/LTIs An analysis of documents for studies of CYP with LLC/LTIs submitted for research ethics committee (REC) review Interviews exploring REC member experiences of reviewing research involving CYP with LLC/LTIs Results: To date, three work-packages have been completed. The systematic review found that recruitment information is consistently underreported in studies involving CYP with LLC/LTIs, making it difficult to assess potential bias. Barriers identified in the survey of clinicians included time and resources; attitudes to research; clinicians' perspectives of the families; and the REC review process. Similar issues were identified by CIs in the national survey, where ethical and regulatory processes, access to families, and funding were viewed as barriers to research with CYP with LLC/LTIs. Conclusion: Clinicians and researchers continue to identify multiple barriers to involving CYP with LLC/LTIs in research. These barriers may be clinician driven, resource-based, or due to regulatory and REC review processes. Findings from the BRAVES project will facilitate the development of guidance for overcoming these barriers.